Children, futurity, and value: Adventures of Huckleberry Finn. Issue 1 (2nd January 2016) - Stoneley, Peter
Abstract : A recurrent but relatively unquestioned element in the canonisation of Adventures of Huckleberry Finn is that the novel is about securing a meaningful way forward for the American child. The sense is that the novel deserves to live and to have a future because it is about a child, and tied in with the need for the young nation to project and to determine its future. This might seem, to apply the terms of queer debate, to lend weight to 'reproductive futurism': the child and 'American family values' are to the fore, while sexual minorities and alternative social models are excluded. The present essay re-reads Huckleberry Finn and Twain's other Huck narratives, using the coordinates of queer theory. The result is a more equivocal picture. Twain does use Huck to assert the rights of the white American family, but he also uses him to explore alternative ideas of social organisation. More fundamentally, Twain increasingly finds that the idea of the child is no longer a sufficient motive for believing in and projecting a future. Rather, his writing leads the reader towards the impossibility of the future, both for the nation and its child.